2014
DOI: 10.1088/0741-3335/56/11/114010
|View full text |Cite
|
Sign up to set email alerts
|

2D interpolation and extrapolation of discrete magnetic measurements with toroidal harmonics for equilibrium reconstruction in a tokamak

Abstract: We present a method based on the use of toroidal harmonics and on a modelization of the poloidal field coils and divertor coils for the 2D interpolation and extrapolation of discrete magnetic measurements in a tokamak. The method is generic and can be used to provide Cauchy boundary conditions needed as input by a fixed domain equilibrium reconstruction code like Equinox [1]. It can also be used to extrapolate the magnetic measurements in order to compute the plasma boundary itself. The proposed method and alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…The spatial distribution of the magnetic flux ψ(r, z) can be decomposed into an infinite series of basis functions f i (see [3] for details). Using the assumption of symmetry of the threedimensional plasma column in the toroidal direction, for each point in the vicinity of the plasma with coordinates (r, z) in the poloidal plane the flux distribution can be decomposed into an infinite series:…”
Section: Plasma Boundary Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distribution of the magnetic flux ψ(r, z) can be decomposed into an infinite series of basis functions f i (see [3] for details). Using the assumption of symmetry of the threedimensional plasma column in the toroidal direction, for each point in the vicinity of the plasma with coordinates (r, z) in the poloidal plane the flux distribution can be decomposed into an infinite series:…”
Section: Plasma Boundary Modelmentioning
confidence: 99%
“…However, full reconstruction of the equilibrium magnetic field (which includes the plasma shape) is a complex task due to non-linear behavior of the plasma. In [3], it was shown that the plasma boundary can be modeled by a linear combination of a specific kind of basis functions. Since the basis functions are known, the estimation problem can be formulated as a simple linear regression with a potentially infinite number of regressors.…”
Section: Introductionmentioning
confidence: 99%
“…The number of harmonics to be used need not be large to obtain precise fit to the measurements. 9 Typically the order of the harmonics is chosen to be 4, 5 or 6. Figure 2 shows a WEST example case of boundary reconstruction with the code using toroidal harmonics only (called VacTH).…”
Section: Iiia the Toroidal Harmonics Expansionmentioning
confidence: 99%
“…This is done by least square fitting a truncated series of toroidal harmonic functions to the magnetic measurements. In principle this first step can be sufficient to determine the plasma boundary [2][3][4][5][6][7][8][9] (also see the review article 10 ). Indeed the toroidal harmonics expansion is valid anywhere in the vacuum surrounding the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, FREEBIE is used in the so-called inverse mode, which predicts PF coils currents from a give plasma boundary and profiles. The third code employed in this study is VacTH [4], which provides a fast reconstruction of the plasma boundary from magnetic measurements using a toroidal harmonics basis.…”
Section: Introductionmentioning
confidence: 99%